1981
DOI: 10.1111/j.1471-4159.1981.tb02398.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Rabbit Brain Cytosolic and Membrane‐Bound Gangliosides During Prenatal Life

Abstract: The present study deals with the developmental profile of cytosolic and membrane-bound gangliosides in rabbit whole brain from the 21st day of pregnancy, the time at which brain could be macroscopically recognized and handled, till birth. In this period of prenatal life the content of membrane-bound gangliosides showed a 2.5-fold increase, referred to fresh and dry brain weight and to membrane-bound protein; the content of cytosolic gangliosides reached a maximum at 21-22 days of pregnancy, and then underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Although the main site of ganglioside deposition is the plasma membrane, small amounts of gangliosides occur in soluble form in the brain of different animals and in cultured cells [2][3][4][5][6][7]. In calf [3] and rat [6] brain cytosolic gangliosides were shown to be present as lipoprotein complexes having varying ganglioside and protein composition.…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…Although the main site of ganglioside deposition is the plasma membrane, small amounts of gangliosides occur in soluble form in the brain of different animals and in cultured cells [2][3][4][5][6][7]. In calf [3] and rat [6] brain cytosolic gangliosides were shown to be present as lipoprotein complexes having varying ganglioside and protein composition.…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…1996), but very little is known about the mechanisms of escape from the lysosome and the transfer of these intermediates to the Golgi or other cellular districts, nor on the regulation of these processes. The presence of soluble ganglioside/protein complexes in the cytosol reported by some Authors (Sonnino et al. 1979, 1981, 1984; Chigorno et al.…”
Section: Glycosphingolipid Intracellular Traffic and Metabolismmentioning
confidence: 90%
“…1) constitutes the primary type of sialoglycoconjugate in vertebrate neurons and is predominantly localized in the plasma membranes of those cells (Ledeen 1989;Ledeen and Wu 1992). There is also considerable evidence for the existence of intracellular pools (Sonnino et al 1981;Ledeen et al 1988;Gillard et al 1993), which, although quantitatively minor, may fulfill important signaling, transport, and regulatory functions. An early study reported gangliosides as being present in every subcellular fraction of bovine mammary gland and rat liver, the level in nuclei from the latter being comparable to that in total homogenate (Keenan et al 1972).…”
Section: Gangliosides Of the Cell And Nucleusmentioning
confidence: 98%